The burning maze - Riordan, Rick (Riordan, Rick. Trials of Apollo, 2019)
The Greek god Apollo, cast down to earth as the ungifted human teenager Lester Papadopoulos, and his demigod friends must go through the Labyrinth to find the third emperor--and an Oracle who speaks in word puzzles--somewhere in the American Southwest.